Deconstructing The Meaning Of The Representation Of The Sanghyang Gandrung Dance - Trisnawati, Ida ayu (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2018)
This present study explores Sanghyang Gandrung Dance performed at Sidatapa Village, Banjar District, Buleleng, Bali. The qualitative approach was employed to implement the critical ethnography of the existence of Sanghyang Gandrung Dance. The study focuses on the identification of the existence of Sanghyang Gandrung Dance and on the description of the form of its performance and meaning as the dance performed at Sidatapa Village, Banjar District, Buleleng, Bali. The result of the study shows that when Sanghyang Gandung Dance was created and how it has been developed cannot be definitely described; however, its existence at Sidatapa Village cannot be separated from the local people’s belief. It was created and has been performed as an attempt to ward off misfortune. It was created and performed to avoid disaster or epidemic locally referred to as mrana, whereas Gandrung Dance was created and performed to be offered to Gods for the abundant agricultural yield. It has usually been performed before Sanghyang Dance is performed. The ceremonial procession during which they are performed is initiated with several traditional activities, starting from a notification which is made for the local people to get involved in the event when cockfighting is held. Then, the procession, which lasts for 42 days (the Balinese calendar-based one month and seven days), is held. They are performed at night from 7.00 to 10 p.m. Indonesia Central Time. The procession starts with Gandrung Dance, which is performed with 9 dancing movements, and then Sanghyang Dance, which is performed with 11 dancing movements. After lasting for 42 days, the procession is closed with a rite locally referred to as tegen-tegenan procession in which agricultural products are carried by those involved in the procession. Sanghyang Gandrung Dance has religious, social and educational functions. The local people perform it to express their thanks to God, ethics and aesthetics, and to ward off misfortune.